Migration and common mental disorder: An improvement in mental health over time?. (February 2015) - Butler, Margaret; Warfa, Nasir; Khatib, Yasmin; Bhui, Kamaldeep
Abstract Global migration is reaching record high levels and UK migrant groups comprise an increasing proportion of the total population. The migratory process causes stress that can affect mental health. There is limited consistent empirical evidence of a longitudinal nature to explain the association between migration and mental health. This review aims to examine the evidence of a relationship between migration and common mental disorder (CMD) amongst migrants over time. A comprehensive search of medical and psychiatric databases for global quantitative empirical studies investigating incidence of CMD amongst adult migrants from 1975 to July 2012 was conducted. Declines in rates of CMD amongst migrants over time were reported by two thirds of the 18 studies reviewed, less than one third of which were statistically significant. On the contrary, three studies showed an increased rate of CMD, one statistically significant. Individual psychological resources, social support, the acculturation process, cultural variations and time since relocation are identified as statistically significant protective factors against the development of CMD amongst migrants. New enlightening points include the significant impact of varying patterns of psychological distress, of which negative is the most adverse for CMD. Migration is an extremely complex process. Further clarification is needed to gain deeper understanding of the relationship between migration and CMD to address contradictions in the literature and health inequalities amongst migrants.